2021
DOI: 10.5937/bastina31-34257
|View full text |Cite
|
Sign up to set email alerts
|

The emotions in the educational context and quality assessment of ongoing platforms for online teaching on the territory of Kosovo and Metohija

Abstract: У раду је испитативана изражаност позитивних и негативних емоција средњошколаца из Косовске Митровице (Н=100) у току онлајн наставе као и њихова веза са проценама квалитета онлајн платформи за наставу на даљину. Коришћени инструменти: Упитник емоција постигнућа (AEQ), Упитник о процени квалитета постојећих платформи за онлајн наставу (УПКПОН1) и Упитник социодемографских варијабли. Резултати су показали да се током онлајн наставе интензивније доживљавају позитивне емоције (уживање, понос, олакшање) у одн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…An interesting finding showed that experiencing positive and negative emotions during online learning does not significantly correlate with academic achievement Simić, J., Ranđelović, D., & Šoškić, R. (2024). Emotions in education -concept, models, and correlates, SCIENCE International journal, 3(2), 139-144. doi: 10.35120/sciencej0302139s UDK: 378.22.015.3:159.942 (Ranđelović & Mihajlović, 2021). Some authors have investigated the role of academic emotions in the relationship between perceived academic control and self-regulated learning within online learning and found that boredom and anxiety have significant moderating effects on self-regulated learning; in other words, good self-regulation requires perceived control and fewer negative emotions (Jiwon & Myunghee, 2014).Meta-analysis results have shown that teacher support is significantly correlated with students' academic emotions, and these relationships are moderated by culture, age, and gender.…”
Section: The Correlates Of Academic Emotionsmentioning
confidence: 99%
“…An interesting finding showed that experiencing positive and negative emotions during online learning does not significantly correlate with academic achievement Simić, J., Ranđelović, D., & Šoškić, R. (2024). Emotions in education -concept, models, and correlates, SCIENCE International journal, 3(2), 139-144. doi: 10.35120/sciencej0302139s UDK: 378.22.015.3:159.942 (Ranđelović & Mihajlović, 2021). Some authors have investigated the role of academic emotions in the relationship between perceived academic control and self-regulated learning within online learning and found that boredom and anxiety have significant moderating effects on self-regulated learning; in other words, good self-regulation requires perceived control and fewer negative emotions (Jiwon & Myunghee, 2014).Meta-analysis results have shown that teacher support is significantly correlated with students' academic emotions, and these relationships are moderated by culture, age, and gender.…”
Section: The Correlates Of Academic Emotionsmentioning
confidence: 99%